The mediating effect of audit quality on the relationship between corporate governance mechanisms and financial reporting quality - Qawqzeh, Hamza Kamel Okleh
The incessant manipulations of corporate financial statements globally in the past few years have led to several scandals and failur s. This phenomenon has resulted in serious threats to the reliability of financial reporting and external audit arising from lack of integrity and credibility of audited financial statements. This is attributed to the negligence and inability of external auditors to alert shareholders of such manipulation and misleading in the financial statements and reporting ofthese violations. The decrease in the financial reporting quality (FRQ) is mostly attributed to the increasing of discretionary accruals estimated by the management. Hence, the current study aimed at investigating the influence of the external auditor's characteristics and corporate governance (CG) mechanisms on the arning management and FRQ, and the mediating effect of the audit quality on these relationships in the Jordanian context. The secondary data of 180 public-list d firms in Amman Stock Exchange from 2009 until 2017 were gathered through annual reports of the companies and Datastream databa . Multiple regression technique and diagnostic analysis were performed to test all assumptions for the data to be valid. In this study, discretionary accruals (DACC) are used as a measurement of FRQ, giv n that the DACC capture the earnings management and thus, provides an inverse proxy for FRQ. By using balanced panel data and an econometric analysis to select the best method among the Fixed, Random or Pooled OLS Effects through Eviews software, the Fixed Effect is found to be the best specification method for all of the study models. Findings of the first model indicated that auditor size, indu tr specialization auditor tenure, board size, board independence, directors' remunerations, family and directors' ownership have significantly given impact on FRQ. Meanwhile board expertise, institutional and managerial ownership have insignificant impact on FRQ. Findings of the second model showed that industry specialization, auditor tenure, board size, expertise, directors' remunerations, directors ownership, institutional and managerial ownership have significant effects on audit quality. While auditor size, board indep ndence and family ownership have insignificant influence on audit quality. Finally, in terms of the mediating effect in the third model, the study employed two complementary methods, namely the Causal Steps Method and the Sobel test. The results of the mediation model revealed that audit quality mediates the relationship between CG I gchanisl11s and FRQ. The CUlT nt study created new understanding and perspective of th interaction between ownership structure, auditor's characteristics, board components, audit quality, earnings management and FRQ. The findings are important to the policy makers, professionals and regulatory bodies, especially with regards to external audit quality and mandating and developing of the CO mechanisms. These findings can be applied to other developing countries that have similar economic and political environment with Jordan.